Narratives of Performance Assessment-Based Competency Testing for Measuring Students' Programming Competencies - Erwinsyah Simanungkalit; Jenny Sari Taringan; Mardhiatul Husna; Djames Siahaan (International Journal of Educational Narratives, 2026)
Background. Programming competence is a fundamental skill for students in information technology education. Despite its importance, assessment practices continue to rely predominantly on theoretical examinations that inadequately represent students’ practical abilities to solve authentic programming problems. Purpose. This study aims to explore the narratives of performance assessment-based competency testing for measuring students’ programming competencies through an authentic and comprehensive assessment model that captures both learning processes and performance outcomes. Method. This study employed a quantitative approach using a quasi-experimental design supported by a literature review. Performance assessment narratives were developed from students’ competency test results using a structured rubric encompassing four dimensions: algorithm planning, code implementation, debugging, and program optimization. Results. The findings reveal narratives of students’ programming competency development that are more comprehensive than those generated through conventional assessment methods. The performance assessment model demonstrated greater accuracy in evaluating authentic programming competencies. Students achieved the highest performance in code implementation, whereas debugging and program optimization emerged as the primary challenges. Furthermore, the assessment narratives provided deeper insights into students’ critical thinking, problem-solving abilities, creativity, and the progression of their programming skills.   Conclusion. he narratives generated through performance assessment-based competency testing offer an authentic and effective evaluation framework for measuring students’ programming competencies. Beyond providing reliable evidence of learning outcomes, these narratives deliver meaningful feedback that supports continuous competency development and better prepares students to meet the professional demands of the information technology industry.